Suitability of stability assessment methods for topical formulations enriched with apple pomace extract - Katarzyna Czerniewicz; Anna Olejnik; Maria Urbańska; Karolina Latanowicz; Justyna Gornowicz-Porowska; Krzysztof Kus (PLoS ONE, 2026)
The cosmetic industry has shown a growing interest in incorporating natural ingredients derived from food waste due to their perceived benefits and consumer preference for eco-friendly and sustainable products. Apple pomace, a by-product of apple juice and cider production, is rich in bioactive compounds such as polyphenols, mainly flavonoids and triterpenoids, offering antioxidant, anti-aging and anti-inflammatory benefits. The study aimed to develop and compare the stability of topical formulations containing apple pomace extract, including a cleansing gel, a serum, and a face cream (1%, 3% and 2% w/w extract, respectively), formulated in stable (A) and unstable (B) variants and to assess the effectiveness and efficiency of advanced stability testing methods for cosmetics. The key distinction in cleansing gels was the use of either Guar Hydroxypropyltrimonium Chloride or Cyamopsis Gum Tetragonoloba; in serums, stability depended on xanthan gum or Cyamopsis Gum Tetragonoloba; and for face creams, the critical factor was the incorporation of Cetearyl Olivate and Sorbitan Olivate. Formulations were stored for 30 days at 4°C, 25°C, and 45°C and analyzed using multiple light scattering (MLS), laser diffraction (LD) and optical microscopy. MLS confirmed high stability of all A variants, with negligible fluctuations in their transmission/backscattering profiles, whereas B variants exhibited pronounced instability reflected by marked changes in transmission signals (up to 58.6%). Optical microscopy confirmed these findings, with homogeneous droplet distribution in Cream A and heterogeneous coalescence in Cream B. These results demonstrate that MLS and LD were suitable for detecting changes in both emulsions and hydrogels, whereas optical microscopy was effective only for emulsions. The application of these advanced stability measurement techniques can enhance cosmetic formulation design and support sustainable cosmetic development.